Correction: Bioaccessibility and biotransformation of anthocyanin monomers following in vitro simulated gastric-intestinal digestion and in vivo metabolism in rats. Issue 7 (17th June 2020) - Chen, Yao; Chen, Hui; Zhang, Weijie; Ding, Yangyang; Zhao, Ting; Zhang, Min; Mao, Guanghua; Feng, Weiwei; Wu, Xiangyang; Liuqing Yang,
Abstract : Correction for 'Bioaccessibility and biotransformation of anthocyanin monomers following in vitro simulated gastric-intestinal digestion and in vivo metabolism in rats' by Yao Chen et al., Food Funct., 2019, 10, 6052–6061, DOI: ; 10.1039/C9FO00871C .